High‐Performance and Environmentally Stable Planar Heterojunction Perovskite Solar Cells Based on a Solution‐Processed Copper‐Doped Nickel Oxide Hole‐Transporting Layer. (29th November 2014) - Kim, Jong H.; Liang, Po‐Wei; Williams, Spencer T.; Cho, Namchul; Chueh, Chu‐Chen; Glaz, Micah S.; Ginger, David S.; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> An effective approach to significantly increase the electrical conductivity of a NiOx hole‐transporting layer (HTL) to achieve high‐efficiency planar heterojunction perovskite solar cells is demonstrated. Perovskite solar cells based on using Cu‐doped NiOx HTL show a remarkably improved power conversion efficiency up to 15.40% due to the improved electrical conductivity and enhanced perovskite film quality. General applicability of Cu‐doped NiOx to larger bandgap perovskites is also demonstrated in this study. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>